Identification of Gastrointestinal Parasite in Hospitalized Cats at Several Animal Clinics in Surabaya Using Faecal Examination Method - Luthfiyyah Nur Afifah Siswandi; Agus Sunarso; Iwan Sahrial Hamid; Mufasirin; Nusdianto Triakoso (Universitas Airlangga, 2023)
The aim of this study is to identify the parasite species and prevalence of gastrointestinal parasites that infect cats hospitalized at several veterinary clinics in Surabaya using the faecal examination method. The type of this research is an observational with research design used in this study is a cross sectional study. The samples used in this study were 100 cat feces that were hospitalized at several veterinary clinics in Surabaya and each took 25 fecal samples. This sample was examined using native, sedimentation, and floating methods. The results showed 35% of samples were positively infected by gastrointestinal parasites with 28% parasites as single infection and 7% as mixed infection. The gastrointestinal parasites that identified in this study were Toxocara cati, Ancylostoma sp., Cryptosporidium sp., Isospora felis, and Isospora rivolta. The results of statistical analysis with chi square test showed that sex and age were not related to the prevalence of the gastrointestinal parasites in hospitalized cats at several animal clinics in Surabaya.